PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN ILEGAL SATWA LIAR YANG DILINDUNGI BERDASARKAN UNDANG – UNDANG NOMOR 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSISTEMNYA DI WILAYAH HUKUM DITRESKRIMSUS POLDA RIAU - Tri Saputra; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Riau Province is one of the areas with natural resources is very high. The condition is directly aligned with the number of criminal acts of illegal trade in wildlife. Based on this understanding, the authors formulated two formulation of the problem, namely: First, Do causes of the illegal trade in wildlife is protected pursuant to Act No. 5 of 1990 on Conservation of Natural Resources and Ecosystems in the jurisdiction Ditreskrimsus Riau Police ?. Second, How the criminal responsibility of the perpetrators of criminal acts illegal trade in wildlife is protected pursuant to Act No. 5 of 1990 on Conservation of Natural Resources and Ecosystems in the jurisdiction Ditreskrimsus Riau Police ?.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the problems to be studied. This research was conducted in Ditreskrimsus Riau Police, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data terier, technical data collection in this study with interviews and literature study then analyzed qualitatively and process data and generate descriptive data and then infer deductively.From the research problem there are two main things that can be summed up as follows: First, the factors that cause illegal trade in wildlife is protected pursuant to Act No. 5 of 1990 on Conservation of Natural Resources and Ecosystems in the jurisdiction Ditreskrimsus Riau Police, Lack on public awareness and knowledge of wildlife, economic factors being one of the very important, conflict between people and wildlife, high demand from buyers, and less specifically punishment or sanctions given to the perpetrators of criminal acts. Second, the criminal responsibility of the perpetrators of the crime of illegal trade in wildlife is protected pursuant to Act No. 5 of 1990 on Conservation of Natural Resources and Ecosystems in the jurisdiction Ditreskrimsus Riau Police.Keywords: Criminal Liability – Crime - Illegal Trade in Wildlife